2013
DOI: 10.1007/s11010-013-1845-x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reverses multidrug resistance and epithelial–mesenchymal transition (EMT) via activating AMP-activated protein kinase (AMPK) in human breast cancer cells

Abstract: Breast cancer is the most frequently diagnosed tumor type and the primary leading cause of cancer deaths in women worldwide and multidrug resistance is the major obstacle for breast cancer treatment improvement. Emerging evidence suggests that metformin, the most widely used antidiabetic drug, resensitizes and cooperates with some anticancer drugs to exert anticancer effect. However, there are no data regarding the reversal effect of metformin on chemoresistance in breast cancer. In the present study, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 38 publications
3
109
0
2
Order By: Relevance
“…AMPK causes cell cycle arrest in certain cancer cell lines such as hepatoma HepG2, prostate carcinoma PC-3 and breast cancer MCF-7 by up-regulating tumor suppressor genes such as p53, p21 and p27 [33][34][35]. Similar to these reports, we observed that the suppressive effect of OA and/or ALA on esophageal cancer cell proliferation was mediated by activation of AMPK and/or decreasing phosphorylation of S6.…”
Section: Discussionsupporting
confidence: 88%
“…AMPK causes cell cycle arrest in certain cancer cell lines such as hepatoma HepG2, prostate carcinoma PC-3 and breast cancer MCF-7 by up-regulating tumor suppressor genes such as p53, p21 and p27 [33][34][35]. Similar to these reports, we observed that the suppressive effect of OA and/or ALA on esophageal cancer cell proliferation was mediated by activation of AMPK and/or decreasing phosphorylation of S6.…”
Section: Discussionsupporting
confidence: 88%
“…Evidence is beginning to emerge that several ABC transporters contain binding sites for EMT regulators, such as Twist, Snail, Slug, FOXC2, and E12/E47 [46], and at least 3 of these factors, Snail, Twist, and FOXC2, can modulate the promoter activity of ABC transporters. Interestingly, an activated Ras oncogene, which is a potent activator of the AMPK pathway, has been found to partly abolish resensitization and preserve EMT in MCF7/5-fluorouracil and MDA-MB-231 cells [47]. The authors of this study also discovered that the antidiabetic drug metformin had the ability to reverse MDR by inhibiting EMT.…”
Section: Emt In Signal Transduction Pathways and Drug Resistancementioning
confidence: 83%
“…However, AMPK activation by metformin inhibits the migration and invasion of melanoma cells [40] . Moreover, a recent study showed that metformin reverses EMT via the activation of AMPK in human breast cancer cells [41] . Accordingly, it seems that the role of AMPK in cell metastatic potential may be dependent on the type of stimulus or the cell that is used in the assay.…”
Section: Discussionmentioning
confidence: 99%